PERUBAHAN SOSIAL KEDUDUKAN DAN PERAN MAMAK TERHADAP ANAK DAN KEMENAKAN DI RANAH MINANG - Sri Natin (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2008)
The result of this research proved that origin of mother’s position and role is very closed to the child and nephew/niece because the cultural concept based on equality of status among human being makes the harmony of life between man and woman. Because of the position of sumondonese is not as high as one in community of Patriarkhi to encourage obtaining child (quality of self competence of knowledge and science) by wandering. The social change of mother’s position and role is likely caused by 2 reasons; Different view of phenomenon that nature must change, time must rotate and experience is a teacher. Change of father’s position as sumondonese (the honor guest) becomes a father in family of Batih. The improvement of education and social status of nephew/niece, some mothers feel reluctant to guide the nephew/niece. Less intensity of relation is caused by far distance of residence, meanwhile the economic condition is very limited, caused by  mother’s various activities as well. Change of relative member’s behavior is caused by lack of attention and care or mother may be sel. sh, therefore the faithfulness of nephew/niece decreases.